Evaluation of the Implementation of the Revitalization Program in Preservation of Van Den Bosch Fortress in Ngawi - Bayu Hermawan; Arif Budi Sholihah; Putri Ayu Pramanasari (Talenta Publisher, 2019)
One of the relics of Dutch colonial buildings in Indonesia is the Van Den Bosch Fortress, this fortress has a revitalization program that is in line with the heritage city program of the Direktorat Jendral Penataan Ruang Pekerjaan Umum dan Perumahan Rakyat Republik Indonesia (PUPR). The purpose of this study is to evaluate the extent of the implementation of revitalization to increase the benefits and direction of preservation of the fortress, and to support Ngawi Regency as a conservation activity for the Cultural Heritage City as the main strategy for urban development. Revitalization evaluation techniques are seen based on the level of vitality of the built area which includes several aspects such as decreasing physical quality of buildings, regional images, economic and activity social. The writer used the descriptive qualitative method by collecting data related to Fort Van den Bosch, then data analyzed by using the Miles and Huberman method. The results of the evaluation study found the implementation of the Van Den Bosch Fortification revitalization program encountered several obstacles and the revitalization program was divided into 2, such as the core of building of the fort and the development of the fort area environment. Keyword: Van Den Bosch Fortress, Evaluation, Conservation, Revitalization